Characteristics of genetic mineralogy of pyrite and quartz and their indicating significance in the Gaosongshan Gold Deposit, Heilongjiang Province, NE China - Huiqing Geng; Xuexiang Gu; Yongmei Zhang (Earth Sciences Research Journal)
The Gaosongshan epithermal gold deposit in Heilongjiang, Northeast China, is hosted by the Lower Cretaceous intermediate-basic volcanic rocks. Three auriferous quartz veins including eleven gold orebodies were all discovered in tectonoclastic zones. Genetic mineralogy study including the thermoelectricity, rare earth elements and trace elements of pyrite and rare earth elements of quartz were carried out. Thermoelectric conductive type of pyrite is mainly N-P type. Calculating the thermoelectric parameters XNP and denudation percentage γ of pyrites from orebodies 1-I, 2-II and 2-IV, suggests that gold orebodies are all eroded to their middle-lower parts. The variable range of Co concentrations (51.3-264.0ppm) and Ni concentrations (68.9-258.0ppm) and Co: Ni ratio (0.31-1.90), together with relatively small Sr/Ba ratio in ore-bearing pyrites (0.11-0.50), supports a hydrothermal origin of mineralization at Gaosongshan gold deposit. Compared with volcanic rocks, the chondrite-normalized REE patterns of ore-bearing pyrites and quartz are all LREE enriched with similar ΣLREE/ΣHREE ratio ranging from 7.37-13.68 in ore-bearing pyrites, 4.74-15.37 in ore-bearing quartz and no Ce anomalies. δEu values in ore-bearing pyrites and quartz are 0.65-1.66 (average=0.93) and 0.66-1.62 (average=1.03), respectively. δEu values of volcanic rocks are 0.861.07 (average 0.94), suggesting no obvious negative Eu anomalies. Similar REE characteristics of ore-bearing pyrites and quartz and volcanic rocks, together with previous oxygen and hydrogen isotope studies of quartz, suggest that the ore-forming fluids of the Gaosongshan gold deposit were mainly magmatic origin which was associated with andesitic magma and was partly mixed with atmospheric water. Comparing trace elements characteristics of ore-bearing pyrites with volcanic rocks, together with previous S isotopic studies, it is concluded that the ore-forming materials were derived from the surrounding rocks. Slight changes of Y/Ho (23.8027.28), Zr/Hf (35.4147.83), Nb/Ta (10.9618.52) in ore-bearing pyrites indicate that the ore-forming fluid system is relatively stable during the ore-forming process.